PENINGKATAN PENDAPATAN MASYARAKAT DENGAN PRODUK PERMEN PINANG (PERANG) PADA DESA TELUK SENTOSA - Zulkarnain Nasution; Tiwi Eviliani; Heni Mardianti (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Increasing Income Through Betel Nut Candy Products (PERANG) in Teluk Sentosa Village aims to provide a deep understanding to the community about the significant potential of local products, particularly betel nut, which is known for its health benefits and high economic value. In this outreach program, the community received training on making betel nut candy conducted in a participatory manner, where the entire processing was done together with guidance from experts. The activities began with an introduction to the benefits of betel nut, both from a health perspective, such as its high antioxidant content, and from an economic standpoint, which can enhance household income. Through this training, village residents were encouraged to develop their creativity in creating more attractive and high-value product variants. As a subsequent step, it is hoped that these betel nut candy products can enter larger distribution networks, including modern and online markets, thereby providing a more significant economic impact for the community of Teluk Sentosa Village. This program also plans to involve more community groups in further training, allowing more families to benefit economically from these innovative products.